Visual Language of Angling Dharma Relief at Jago Temple - Wardaya, Marina; Mudra, I Wayan; Udayana, A. A. Gde Bagus; Suardina, I Nyoman (VCD: Journal of Visual Communication Design, 2024)
The relief panels depicting the Angling Dharma story on the Jago Temple offer a valuable resource for researchers, similar to the Kresnayana story reliefs in Prambanan. These reliefs serve as visual narratives, conveying the Angling Dharma epic. The sculptors meticulously selected key scenes from the text, translating them into captivating visuals and arranging them within individual panels. These panels, when assembled, form a cohesive narrative of the Angling Dharma story. In a modern context, this sequence of panels resembles a movie, unfolding the story through a series of images. To encompass the entirety of the narrative within the confines of the relief's surface, the sculptors employed a distinct drawing method known as the "space-time-flat" system. This approach differs significantly from modern Western artistic conventions. The unfamiliar style can pose challenges in interpreting the depicted scenes. This research proposes a descriptive and qualitative analysis of the "space-time-flat" method used in the Angling Dharma reliefs. By delving into this unique drawing system, the study aims to glean valuable insights that can be applied in the creation of various visual media. The analysis can shed light on artistic practices that predate the arrival of Western drawing techniques with their emphasis on naturalism, perspective, and single-moment depiction.